Psychosocial and Behavioral Dimensions of Zakat in Malaysia: A Thematic Literature Analysis - Abdullah, Muhammad Saffuan; Salleh, Hishamudin; Rusdi, Muhammad (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2026)
Zakat is a central pillar of the Islamic socio-economic system aimed at promoting social justice and human well-being. In Malaysia, zakat research has traditionally focused on institutional governance and distribution efficiency. However, recent studies increasingly explore the human impact of zakat, particularly from psychosocial and behavioral perspectives. This study synthesizes recent zakat research in Malaysia by examining the psychosocial and behavioral dimensions associated with zakat recipients, zakat payers, and zakat institutions. Using a qualitative literature review approach, this study analyzed 20 empirical and conceptual articles published between 2021 and 2025. Relevant studies were identified through database searches in Google Scholar, Scopus-indexed journals, and regional academic databases using keywords related to zakat, psychosocial well-being, zakat compliance behavior, and zakat institutions in Malaysia. The selected studies were screened for titles, abstracts, and full texts before being coded and analyzed using thematic analysis. The findings reveal four dominant themes in the literature: psychosocial well-being of zakat recipients (asnaf), psychological determinants of zakat payment behavior, counseling and psychosocial support within zakat institutions, and innovation in zakat distribution systems. The analysis shows that research on zakat payment compliance remains dominant, while studies examining psychosocial recovery and empowerment among zakat recipients remain limited. In addition, counseling-based interventions within zakat institutions are still rarely examined empirically. These findings suggest the need for more holistic zakat research that integrates economic, psychological, social, and spiritual perspectives. Future studies should explore intervention-based models and empowerment-oriented approaches to strengthen zakat's role in sustainable human development.